The effect of Mg2+ on Ca2+ binding to cardiac troponin C in hypertrophic cardiomyopathy associated TNNC1 variants. (2nd August 2022) - Rayani, Kaveh; Hantz, Eric R.; Haji‐Ghassemi, Omid; Li, Alison Y.; Spuches, Anne M.; Van Petegem, Filip; Solaro, R. John; Lindert, Steffen; Tibbits, Glen F.
Abstract : Cardiac troponin C (cTnC) is the critical Ca 2+ ‐sensing component of the troponin complex. Binding of Ca 2+ to cTnC triggers a cascade of conformational changes within the myofilament that culminate in force production. Hypertrophic cardiomyopathy (HCM)‐associated TNNC1 variants generally induce a greater degree and duration of Ca 2+ binding, which may underly the hypertrophic phenotype. Regulation of contraction has long been thought to occur exclusively through Ca 2+ binding to site II of cTnC. However, work by several groups including ours suggest that Mg 2+, which is several orders of magnitude more abundant in the cell than Ca 2+, may compete for binding to the same cTnC regulatory site. We previously used isothermal titration calorimetry (ITC) to demonstrate that physiological concentrations of Mg 2+ may decrease site II Ca 2+ ‐binding in both N‐terminal and full‐length cTnC. Here, we explore the binding of Ca 2+ and Mg 2+ to cTnC harbouring a series of TNNC1 variants thought to be causal in HCM. ITC and thermodynamic integration (TI) simulations show that A8V, L29Q and A31S elevate the affinity for both Ca 2+ and Mg 2+ . Further, L48Q, Q50R and C84Y that are adjacent to the EF hand binding motif of site II have a more significant effect on affinity and the thermodynamics of the binding interaction. To the best of our knowledge, this work is the first to explore the role of Mg 2+ in modifying the Ca 2+ affinity of cTnC mutations linked to HCM. Our results indicate a physiologically significant role for cellular Mg 2+ both at baseline and when elevated on modifying the Ca 2+ binding properties of cTnC and the subsequent conformational changes which precede cardiac contraction. Abstract : Cytosolic‐free Mg 2+ is ~ 1000 times more abundant than Ca 2+ and also binds competitively to Site 2 within cardiac troponin C. Site 2 is the regulatory element of the contractile apparatus and any Mg 2+ binding to this site can interfere with cardiac contraction. Disease states such as Hypertrophic Cardiomyopathy and/or ischemia may skew the Ca 2+ /Mg 2+ binding competition for this site and have significant functional consequences for cardiac force production.